Maternal willingness to pay for infant and young child nutrition counseling services in Vietnam - Nguyen, Phuong Hong; Hoang, Mihn V.; Hajeebhoy, Nemat; Tran, Lan Mai; Le, Chung H.; Menon, Purnima; Rawat, Rahul (Taylor and Francis, 2015)
Background